Effect of Physical Education and Play Applications on School Social Behaviors of Mild-Level Intellectually Disabled Children - Atike Yılmaz; Fikret Soyer (MDPI AG, 2018)
The aim of this study was to examine the influences of physical education and play practices on the school social behavior of mild-level intellectually disabled children. The quantitative research methods used were based on the pre-test, post-test, post-test-retention control group model and the general screening model. A simple random sampling type was used when constructing the sample group. To determine school social behavior, the School Social Behavior Scale (SSBS) was used. Physical education and play lessons were applied for two hours per week for 24 weeks with the purpose of obtaining data from these scales when applied to participants. The study sample group included 20 mild-level intellectually disabled children (14 boys, 6 girls), aged seven to nine years, who were trained at the Special Education and Rehabilitation Center that serves the County of Kocaeli, in the district of Izmit, Turkey. According to the results of the SSBS, we found a statistically significant difference (p < 0.05) between the social competence of present persons’ interpersonal relations, self-control, and academic skills, and the aggressive-nervous persons in the sub-dimensions of negative social behaviors, in favor of the test group. However, no significant difference (p > 0.05) in the antisocial-aggressive and destructive-demanding sub-dimensions was observed. We found that 24-week physical education and playing practices applied to mild-level intellectually disabled children had effects on children’s school social behavior.